Finanacial Resources as Determinants of Academic Performance in Public Secondary Schools in Kuria East and Kuria West Sub-Counties, Kenya - Othoo, Hezekiah Adwar; Olel, Maureen A.; Gogo, Julius (American Journal of Social Sciences and Humanities, 2019)
Shortages and improper utilization of fianancial resources in educational institutions have been found to hinder educational outcomes.This study sought to determine the influence of the levels of adequacy and utilization of financial resources on learners’ academic performance in Kuria East and Kuria West sub counties. The study adopted a descriptive survey research design. The population consisted of 40 principals and 345 teachers. Saturated random sampling technique was used to select 36 principals while stratified random sampling was used to select 138 teachers for the study. Data was collected through questionnaires, document analysis guide and observation checklist. Quantitative data was analyzed using both descriptive and inferential statistics involving percentages, mean and linear regression and qualitative data using content analysis. Findings indicated that adequacy of financial resources influences the performance with a regression coefficient of 0.100 and utilization of financial resources 0.799. From the findings it was concluded that levels of adequacy and utilization of financil resources had statistically significant effects on academic performance in public secondary schools of Kuria east and Kuria west sub-counties.The study recommended that the principals and parents should ensure adequacy and optimal utilization of financial resources. Findings of the study may be useful to Kuria East and Kuria West sub counties, county government of Migori, Teachers Service Commission, educational planners, policy makers, and educational managers to utilize educational financial resources efficiently and device measures to address shortages of educational resources in schools so as to improve academic performance and to academicians for research purposes.